INCIDENCE OF EXTENDED SPECTRUM BETA LACTAMASE PRODUCERS IN CONTACT SURFACES OF MEAT AND MEAT PRODUCTS VENDORS IN KANO METROPOLIS - DAHIRU A. T.; SHAMSUDDEEN U.; MUKHTAR M. D. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
Extended Spectrum Beta Lactamases (ESBLs) are enzymes produced by certain types of bacteria which break down the active ingredients in many of the common antibiotics making them inactive or ineffective. There are atleast two hundred (200) different types of ESBL enzymes documented. The first infection of ESBL was reported in Greece in 1960s. Infections with Extended Spectrum Beta Lactamases (ESBLs) producing organisms are of great clinical significance because of their association with refractile diseases in humans. It is therefore epidemiologically important to public health to continue survey for the incidence of ESBLs from hands, knives and tables of meat and meat products vendors in Kano metropolitan. A total of 96 swab samples of hands, knives and tables (32 of each) of fresh meat, Balangu,Kilishi and Tsire vendors at different retailing points in Kano metropolis were randomly collected using sterile swab sticks. Direct culture method using Eosin Methylene Blue Agar was employed for the detection of enteric bacteria. Isolates were identified using biochemical tests. Clinical Laboratory Standard Institute Break Point procedure was used to confirm antimicrobial susceptibilities. From the 96 swab samples analyzed, the following organisms were isolated Enterobacter aerogenes 5(14.29%), E-coli 17(48.57%), Klebsiella pneumoniae 8(22.86%), Proteus mirabilis 3(08.67%), Salmonella species 2(05.71%). Also, 12(34.29%) of the organisms were isolated from hands with the following percentages: Enterobacter aerogenes 2(16.67%), E-coli 4(33.33%), Klebsiella pneumoniae 4(33.33%), Proteus mirabilis 1(08.33%) and Salmonella species 1(08.33%). 11(37.14%) organisms were detected from knives and reads as follows: Enterobacter aerogenes 2(18.18%) E-coli 6(54.54%), Klebsiella pneumoniae 2(18.18%), Salmonella species 1(09.09%). 12(34.29%) organisms were isolated from the tables which include Enterobacter aerogenes 1(08.33%), E-coli 7(58.33%), Klebsiella pneumoniae 2(16.67%) and Proteus mirabilis 2(16.67%). Twelve 12(34.29%) of the enteric bacteria isolates were confirmed ESBLs positive. Statistical analysis shows no significant difference in the incidence of ESBLs among the different samples. It is recommended that hands and tables should be sanitized and the meat be well protected with nylon leather cloth to prevent meat contamination with enterobacteria.